Wireless Andrew [mobile computing for university campus]. - Hills, A. (IEEE spectrum)
At Carnegie Mellon University in Pittsburgh, staff and students are using mobile computers for various tasks such as transferring lecture notes, sending e-mails, or surfing the net. This possible due to the installation of a wireless network which will cover all 28 academic and administrative buildings on the 40-hectare campus, and provide service to 10000 people. As long as they are on campus, the university community will be able to take advantage of the network. The high speed wireless infrastructure installed at Carnegie Mellon is called Wireless Andrew. Started as a National Science Foundation-funded research network to support Carnegie Mellon's wireless research initiative, the network originally provided coverage in seven campus buildings. The challenges in building such a large network are far from trivial. They include designing the network so that coverage blankets the entire campus, providing enough capacity to handle the campus-wide traffic load. Further, the network must provide highly reliable service. It builds on the university's wired network infrastructure, which currently provides 10-Mb/s and 100-Mb/s Ethernet service. To supply high-speed wireless service to the campus, Lucent WaveLAN equipment has been installed, which uses direct sequence spread-spectrum radio to provide a raw data rate of 2 Mb/s. For wireless access off campus or otherwise out of the range of the WaveLAN network, cellular digital packet data is used